Students With and Without Disabilities Using Social Media: Relationship Benefits and Implications for Education - Greenhow, Christine; Akhmedova, Aisel; Sutcliffe, Jennifer; Fisher, Marisa; Sung, Connie (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2024)
A pandemic in 2020 resulted in economic and social disruption of unprecedented scale. Social distancing — or physical distancing while in public spaces — was required, and social media usage spiked globally as people turned to these online spaces for information and connection. Today’s postsecondary students, in particular, are frequently immersed in social media; it can offer them social supports, such as a greater sense of belonging during times of transition and crisis, but also inherent risks, including cyberbullying and online harassment. Although many studies have examined the social connections or supports for learning that college students without disabilities experience by using social media, few studies have explored these phenomena among college students with disabilities, including neurodevelopmental disabilities such as anxiety disorders (e.g., social anxiety, autism, attention deficit disorder) that make socialization difficult for these young adults. It is important that educational research advances understanding of the socialization experiences of these students with disabilities because students’ sense of belonging and peer support is critical to their engagement and success in K-12 and postsecondary schooling.